Etnopedagogik dalam Pasanggiri Asah Kaparigelan Basa, Sastra, Jeung Budaya Sunda - Syahdiana, Susi Syahdiana. (Puslitjakdikbud Balitbang Kemdikbud, 2018)
AbstractPasanggiri Asah Kaparigelan Basa, Sastra, jeung Budaya Sunda It is a competition for elementary, Junior high school, Senior High School/Vocational School, which is held annually as a form of introduction etnopedagogic to the young generation to preserve the three pillars of culture in Cianjur. The outline of the research problem regarding values, such as moral values, the value of the Sundanese, the character and value of self-actualization Sundanese the components of the Pasanggiri Asah Kaparigelan Basa. Sastra, jeung Budaya Sunda. The purpose of this research is to find out and expose the moral value of Sundanese, the value of Sundanese characters, and the value of self-actualization Sundanese in the component Pasanggiri Asah Kaparigelan Basa, Sastra, jeung budaya Sunda. The methods used, that is descriptive qualitative approach method. Data collection with interview techniques and study the documentation. The results of study to find the value of etnopedagogic with the following conclusion; (1) There is the moral value of Sundanese in components Asah Kaparigelan.(2) There is value in the Sundanese characters in components Asah Kaparigelan. (3) There is the value of self-actualization Sundanese in components Asah Kaparigelan.AbstrakPasanggiri Asah Kaparigelan Basa, Sastra, jeung Budaya Sunda merupakan ajang lomba tingkat SD, SMP, SMA/SMK, yang digelar setiap tahun sebagai wujud pengenalan etnopedagogik kepada generasi muda untuk melestarikan tiga pilar budaya di Kabupaten Cianjur. Rumusan Masalah dalam penelitian ini mengenai bagaimana nilai moral orang Sunda, nilai karakter orang Sunda, dan nilai aktualisasi diri orang Sunda yang terdapat dalam komponen Pasanggiri Asah Kaparigelan Basa. Sastra, jeung budaya Sunda. Tujuan dari penelitian ini untuk mengetahui dan memaparkan tiha hal yaitu; nilai moral orang Sunda, nilai karakter orang Sunda, dan nilai aktualisasi diri orang Sunda yang terdapat dalam setiap komponen lomba (pasanggiri). Metode yang digunakan deskriptif dengan pendekatan kualitatif. Pengumpulan data dengan wawancara dan studi dokumentasi. Dari hasil penelitian ini didapat nilai etnopedagogik dengan kesimpulan berikut; (1) Terdapat nilai moral orang Sunda dalam komponen pasanggiri asah kaparigelan, (2) Terdapat nilai karakter orang Sunda dalam komponen pasanggiri asah kaparigelan (3) Terdapat nilai aktualisasi diri orang Sunda dalam komponen asah kaparigelan.